A comprehensive overview of substance abuse amongst Syrian individuals in an addiction rehabilitation center. Issue 4 (April 2023) - Abazid, Husam; Abu-Farha, Rana; Alsayed, Ahmad R.; Barakat, Muna; Al-Qudah, Raja'a
Abstract: Objectives: This study aims to provide a comprehensive overview of substance abuse amongst Syrian individuals in an addiction rehabilitation center. Methods: This is a descriptive cross-sectional survey-based study, from patients receiving treatment in an addiction rehabilitation center in Damascus. Syria. The study was conducted over a period of nine months. Results: A total of 82 participants were recruited, the majority of them were males (n = 78.95.1%). More than half of those investigated reported multi-level failure (n = 46, 56.1%) during their education. Most of the participants (n = 44, 53.7%) started to use drugs at a friend's home. The family was shown to play a positive role in stopping the initial drug taking trials at early stages (33/56, 58.9%). Again, friends' effect was the main reason for the return of abusing drugs (20/56, 35.7%). Sources of drugs were mainly from drug promoters for most of the participants (n = 58, 70.7%) followed by friends (n = 28, 34.1%). Participants revealed that taking drugs were mostly accompanied by additional habits such as cigarette smoking before using their drugs (n = 65, 79.3%), or drinking alcohol (57.3%). Surprisingly, participants believed that drug abuse does not lead to addiction (n = 52, 63.4%). The most common experienced feeling was depressed, desperate, or sad (n = 47, 57.3%), followed by anxiety and the desire to escape reality and resort to imaginations (n = 44, 53.7%). Conclusions: The findings of this study indicate the need of policymakers to give more attention, in developing preventive strategies, to friends, as a main cause of addiction, in addition to the family influences on individual's drug abuse, addiction behaviors, and mindsets. Understanding the influencing factors could spot the light on the key to solve the addiction problem. A realist rehabilitation programs must be well designed and implemented as the level of individuals, institutions and communities to face this problematic addiction disaster.